2010
DOI: 10.1080/02786821003649352
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an Electrostatic Precipitator with Superhydrophobic Surface when Collecting Airborne Bacteria

Abstract: Modern bioaerosol sampling and analysis techniques that enable rapid detection of low bioagent concentrations in various environments are needed to help us understand the causal relationship between adverse health effects and bioaerosol exposures and also to enable the timely biohazard detection in case of intentional release.We have developed a novel bioaerosol sampler, an electrostatic precipitator with superhydrophobic surface (EPSS), where a combination of electrostatic collection mechanism with superhydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…However, since the sampler is able to perform an efficient collection of 0.3-0.35 μm particles, a wider range of airborne biological agents should be collectible, ranging from viruses to fungi. Following Han's (2008Han's ( , 2010 investigations, it was shown that transfer of biological particles is highly dependant on the composition and volume of the rinsing buffer, while best results were obtained with SDS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, since the sampler is able to perform an efficient collection of 0.3-0.35 μm particles, a wider range of airborne biological agents should be collectible, ranging from viruses to fungi. Following Han's (2008Han's ( , 2010 investigations, it was shown that transfer of biological particles is highly dependant on the composition and volume of the rinsing buffer, while best results were obtained with SDS.…”
Section: Resultsmentioning
confidence: 99%
“…According to the rinsing protocol, the collection efficiency obtained by plate counting in the present study ranges from 57 to 94% when at least 15 ml of liquid is used. Such a volume is commonly used in samplers such as the All Glass Impinger 30 (ACE Glass), the BioSampler R (SKC) and the Coriolis R (Bertin) but it is much higher than volumes used by Han (2008Han ( , 2010. The amount used therefore is a compromise between the recovery efficiency and the sample volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results indicated that the RCS High Flow obtained lower culturable counts than that of the BioSampler due to its higher desiccation factors ). Among various bioaerosol samplers, the electrostatic sampler is increasingly being applied to detect biological aerosols (Yao and Mainelis 2006c;Yao et al 2009b;Han et al 2010). It was shown that when the electrostatic sampler was used, the culturable bioaerosol concentrations could be 5-9 times higher than those obtained by the BioStage impactor (Yao and Mainelis 2006c).…”
Section: Introductionmentioning
confidence: 99%